2021
DOI: 10.3390/healthcare9020143
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Response of Finger Skin Blood Flow during a Braille Character Discrimination Task

Abstract: We hypothesized that age-related changes in sensory function might be reflected by a modulation of the blood flow response associated with tactile sensation. The aim of the present study was to clarify how the blood flow response of the fingers during concentrated finger perception is affected by aging. We measured the tactile-pressure threshold of the distal palmar pad of the index finger and skin blood flow in the finger (SBF) during Braille reading performed under blind conditions in young (n = 27) and olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The age disparity between the elderly inpatients at the long-term stay department and the relatively younger patients at the outpatient clinic could account for this difference. The finger blood flow is decreased in elderly patients, which can explain the more painful and unpleasant experience associated with finger prick, while in adults the finger blood flow allows for a less painful and fast sample with a finger prick (Murata et al, 2021). Another possible explanation could be that outpatients are more open towards microsampling than inpatients and anticipate greater benefits from self-sampling in the comfort of their own homes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The age disparity between the elderly inpatients at the long-term stay department and the relatively younger patients at the outpatient clinic could account for this difference. The finger blood flow is decreased in elderly patients, which can explain the more painful and unpleasant experience associated with finger prick, while in adults the finger blood flow allows for a less painful and fast sample with a finger prick (Murata et al, 2021). Another possible explanation could be that outpatients are more open towards microsampling than inpatients and anticipate greater benefits from self-sampling in the comfort of their own homes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A person's tactile threshold increases with age [35,36]. Atkins et al reported that patients in their 60s were more likely to make mistakes in a VR environment and were slower to move than those in their 20s [26].…”
Section: Discussionmentioning
confidence: 99%